2013
DOI: 10.1037/a0032369
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the severity of intellectual disability in adults: A Mokken scaling analysis of the Learning Disability Screening Questionnaire.

Abstract: A Mokken scaling analysis of the Learning Disability Screening Questionnaire (LDSQ) suggested that, with the exception of 1 item, the scale conforms to the properties of a Mokken scale. This has advantages for estimating the severity of intellectual disability and inferring the difficulties likely to be experienced by an individual for whom there is incomplete information on intellectual and adaptive functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…A single uni-dimensional model was specified, representing the theoretical assumption that the LDSQ measures a uni-dimensional construct of ID. This assumption has been supported in previous psychometric analyses of the LDSQ (Murray & McKenzie, 2013). Further, with only 7 items (6 with 'Read' and 'Write' combined into 'Literacy'); any model with more than one latent variable would have poor factor determination.…”
Section: Statistical Procedures Item Response Theory Analysismentioning
confidence: 65%
See 2 more Smart Citations
“…A single uni-dimensional model was specified, representing the theoretical assumption that the LDSQ measures a uni-dimensional construct of ID. This assumption has been supported in previous psychometric analyses of the LDSQ (Murray & McKenzie, 2013). Further, with only 7 items (6 with 'Read' and 'Write' combined into 'Literacy'); any model with more than one latent variable would have poor factor determination.…”
Section: Statistical Procedures Item Response Theory Analysismentioning
confidence: 65%
“…It is unfortunate that we were unable to assess this item because previous research has suggested that this item is a useful indicator of ID. For example, it has shown a high RUNNING HEAD: Gender Invariance LDSQ discrimination parameter (a scalability coefficient of 0.75 in a Mokken analysis) in previous research (Murray & McKenzie, 2013). Furthermore, because it represents a skill that is relatively easier than the other skills measured by the LDSQ (see the endorsement rates in Table 1), it contributes to the reliable measurement of ID at the more severe levels of impairment.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, Mokken scaling analysis has proven useful in disability research where estimating the severity or predicting the progression of difficulties is a key consideration in understanding and treating a disorder (Kingston et al, 2012;Watson et al, 2012). Similarly, Murray and McKenzie (2013) for a number of reasons: it was developed specifically as a screen for ID; it was designed to have a very short administration and scoring time; it does not require the user to have a particular professional qualification or training; and a series of studies have found it to have good psychometric properties (see section 2.2). In addition, two recent reviews of screening tools that have been used specifically to screen for ID in children (McKenzie & Megson, 2012) and those that have screened for a range of disabilities, including ID (Maulik & Darmstadt, 2007) indicated that none of the reviewed tools displayed sufficiently robust psychometric properties to recommend their use for specific screening for ID in children.…”
Section: Introductionmentioning
confidence: 99%
“…The item selection is based on a nonparametric item response theory (NIRT) model known as the monotone homogeneity model (Sijtsma & Molenaar, 2002, Chapter 2). Mokken scale analysis is used to construct tests in various research areas such as psychology, for assessing psychological distress and well-being (Watson, Wang, Thompson, & Meijer, 2014), depression and anxiety (Bech, Bille, Moller, Hellström, & Ostergaard, 2014), disability in activities of daily living (Kingston et al, 2012), learning disability (Murray & McKenzie, 2013), and sexual sadism (Nitschke, Osterheider, & Mokros, 2009). Mokken scale analysis uses three types of scalability coefficients for assessing the quality of (a) item pairs, (b) individual items, and (c) a set of items.…”
mentioning
confidence: 99%